QUESTIONS ABOUT EDUCATIONAL POLICIES AND REFLECTIONS ON DEMANDS PERCEIVED BY THE BRAZILIAN STATE: TOPICS FOR DETAILED ANALYSIS OF HIS ACTION TOOLS - Lemes, Sebastiao de Souza [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The political propositions of actions and Brazilian state regulation are apparently ineffective in its purpose of meeting the demands of today's society in Brazil. Since the democratization of the country, in the early 1980s in changes function in the action agenda and in order to establish new forms of regulation, the state was structured from issues related to a Brazilian model of development and this position remains, to the best understanding, to the present day. The current educational context is guided and regulated by Law 9394/96 - Law of Directives and Bases of Education and the PNE (Law No. 13,005 / JUNE 2014) - National Education Plan - determines guidelines, goals and strategies for educational policy the next ten years. The knowledge, as a regulatory tool, implies that it is established the kind of knowledge there, then mobilized. Indeed, under this proposal, it seeks to analyze the genealogy of this policy, as cognitive and normative matrix and the possible (or necessary) changes in modes of regulation, considering such instruments as products of policy decisions and the underlying reference as producers of decisions. These regulatory instruments, especially concepts such as guidelines, goals, strategies and regulation, will be used as categories of analysis and as lines of action (Muller and Surel, 2002). This will enable us to verify and analyze the knowledge mobilized for this action (decision) of the state. This is a proposal for discussion and reflection on public policy analysis in the area of education in Brazil now.
Keywords: Educational Policy; Public Policy; Regulatory Instruments